A Nonhybrid Model of Transitioning Pediatric to Adult Critical Care during the Coronavirus Disease 2019 Surge: A Single Unit Experience - Holliday, Kathryn; Horner, Rebecca; Ramesh, Pavanasam; Bebbington, Mark B.; Kanaris, Constantinos (Journal of Pediatric Intensive Care, 2021)
To accommodate the unprecedented demand for critical care beds during the first surge of the coronavirus disease 2019 (COVID-19) pandemic in the United Kingdom, hospitals had to adapt, restructure, and collaborate to provide the best possible care for the pediatric and adult populations. This single-center experience outlines the considerations our hospital took into account when planning for this restructure and the steps taken to ensure a successful execution of the task. Cross-specialty collaboration between the pediatric and adult critical care teams adopted a unique approach to care for only critically ill COVID-19 positive adult patients in the pediatric intensive care unit (PICU), transferring out critically unwell children at an early stage before the adult intensive care unit (AICU) became overwhelmed (nonhybrid model). This was designed to be in a staggered fashion, before allowing the AICU to overflow. This approach enabled the adult critical care team to support pediatric colleagues in learning the nuances of looking after critically ill adults prior to the service being saturated by the predicted supersurge. The success of the operation hinged on two things. First, PICU staff continuing to work in a familiar environment with their usual clinical team and second, the gradual and controlled admission of adult patients into PICU before the peak in demand for critical care beds. This design helped protect staff morale and build confidence in their new clinical role. The overall case fatality of invasively ventilated patients with COVID-19 in our hospital during the first surge was 32%, which is lower than the global average of 45%. This serves as evidence that this nonhybrid model is safe and sustainable.
Keywords: COVID-19; restructure; surge capacity; critical care; pandemic; coronavirus